Peroxisome proliferator‐activated receptor γ coactivator 1‐α overexpression improves angiogenic signalling potential of skeletal muscle‐derived extracellular vesicles. Issue 2 (1st December 2022) - Kargl, Chris K.; Sullivan, Brian P.; Middleton, Derek; York, Andrew; Burton, Lundon C.; Brault, Jeffrey J.; Kuang, Shihuan; Gavin, Timothy P.
Abstract : New Findings: What is the central question of this study? Skeletal muscle extracellular vesicles likely act as pro‐angiogenic signalling factors: does overexpression of peroxisome proliferator‐activated receptor γ coactivator 1‐α (PGC‐1α) alter skeletal muscle myotube extracellular vesicle release, contents and angiogenic potential? What is the main finding and its importance? Overexpression of PGC‐1α results in secretion of extracellular vesicles that elevate measures of angiogenesis and protect against acute oxidative stress in vitro. Skeletal muscle with high levels of PGC‐1α expression, commonly associated with exercise induced angiogenesis and high basal capillarization, may secrete extracellular vesicles that support capillary growth and maintenance. Abstract: Skeletal muscle capillarization is proportional to muscle fibre mitochondrial content and oxidative capacity. Skeletal muscle cells secrete many factors that regulate neighbouring capillary endothelial cells (ECs), including extracellular vesicles (SkM‐EVs). Peroxisome proliferator‐activated receptor γ coactivator 1‐α (PGC‐1α) regulates mitochondrial biogenesis and the oxidative phenotype in skeletal muscle. Skeletal muscle PGC‐1α also regulates secretion of multiple angiogenic factors, but it is unknown whether PGC‐1α regulates SkM‐EV release, contents and angiogenic signalling potential. PGC‐1α was overexpressed via adenovirus in primary human myotubes. EVs were collected from PGC‐1α‐overexpressing myotubes (PGC‐EVs) as well as from green fluorescent protein‐overexpressing myotubes (GFP‐EVs), and from untreated myotubes. EV release and select mRNA contents were measured from EVs. Additionally, ECs were treated with EVs to measure angiogenic potential of EVs in normal conditions and following an oxidative stress challenge. PGC‐1α overexpression did not impact EV release but did elevate EV content of mRNAs for several antioxidant proteins (nuclear factor erythroid 2‐related factor 2, superoxide dismutase 2, glutathione peroxidase). PGC‐EV treatment of cultured human umbilical vein endothelial cells (HUVECs) increased their proliferation (+36.6%), tube formation (length: +28.1%; number: +25.7%) and cellular viability (+52.9%), and reduced reactive oxygen species levels (−41%) compared to GFP‐EVs. Additionally, PGC‐EV treatment protected against tube formation impairments and induction of cellular senescence following acute oxidative stress. Overexpression of PGC‐1α in human myotubes increases the angiogenic potential of SkM‐EVs. These angiogenic benefits coincided with increased anti‐oxidative capacity of recipient HUVECs. High PGC‐1α expression in skeletal muscle may prompt the release of SkM‐EVs that support vascular redox homeostasis and angiogenesis.